Quantitative analysis of the dopamine D4 receptor in the mouse brain - Defagot, Maria Cristina (2000)
The D4 receptor (D4R), a member of the dopamine D2-like receptor family, has been implicated in the pathophysiology of several diseases and has been the target of various investigations regarding its distribution and quantification. The brain distribution of the D4R has been well described in various species, but the quantification is still an issue of controversy, because no specific ligand is commercially available. To circumvent this difficulty we have performed a biochemical and autoradiographical study in brain samples obtained from mice lacking D4Rs and their wild-type siblings; comparison of their binding parameters allows a more accurate quantification of the members of the D2-like receptor family (D2, D3, and D4 receptors). We found that the distribution of D2-like receptors in mouse brain is similar to that of rat brain, i.e., caudate putamen, nucleus accumbens, olfactory tubercle, and hippocampus. The contribution of the D4R to the overall population of D2-like receptors is 17% in nucleus accumbens, 21% in caudate putamen and olfactory tubercle, and 40% in hippocampus. Based on our study we conclude that nemonapride probably binds to nondopaminergic sites that if not properly blocked may lead to overestimations of D4R levels. We observed that the experimental condition that better estimates the density of D4 receptors is the displacement of D2 and D3 [3H]nemonapride binding sites with cold raclopride.